2018
DOI: 10.1001/jamasurg.2017.5461
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Outcomes and Costs After Pediatric Laparoscopic Cholecystectomy

Abstract: The high-volume nature of adult general surgery translated to lower morbidity and cost after pediatric laparoscopic cholecystectomy, suggesting that adult volume is associated with pediatric outcomes. As the rate of pediatric gallstone disease increases, surgeon volume, rather than specialty training, should be considered when pursuing operative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Prolonged obstruction results in inflammation, infection, and even ischemia, resulting in acute inflammation of GB; repeated episodes can result in chronic cholecystitis, in which a thickened GB wall, GB mucosal atrophy and scarring were detected (16). There is no consensus on the management of children with cholelithiasis and the risks of developing complications as a consequence of delaying surgery are well-known (17)(18)(19). More than 70% of cases admitted in emergency became symptomatic when surgery is delayed after a mean time of 38 months.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged obstruction results in inflammation, infection, and even ischemia, resulting in acute inflammation of GB; repeated episodes can result in chronic cholecystitis, in which a thickened GB wall, GB mucosal atrophy and scarring were detected (16). There is no consensus on the management of children with cholelithiasis and the risks of developing complications as a consequence of delaying surgery are well-known (17)(18)(19). More than 70% of cases admitted in emergency became symptomatic when surgery is delayed after a mean time of 38 months.…”
Section: Discussionmentioning
confidence: 99%
“…TG18 advocates definitive surgical intervention (usually laparoscopic cholecystectomy) on the index admission in patients with acute cholecystitis or biliary pancreatitis, citing both prospective longitudinal studies and retrospective observational studies that demonstrated a significantly lower incidence of disease recurrence, hospital readmission, and overall disease-specific complications when the procedure was performed within 7 days of the onset of symptoms in the appropriate patient (recommending within 72 h as preferable) 5,17,[23][24][25][26][27][28][29][30] . However, 15 (60 per cent) of the 25 centres in the present study estimated that less than half of their patients routinely had index admission cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…From 1722, when the first case of cholelithiasis was reported in an autopsy done to a 12-year-old boy, this problem has increasingly interested pediatric surgeons [ 5 , 6 ]. The biliary lithiasis has a multifactorial genesis, with a large family component, characterized by alteration of cholesterol homeostasis and metabolism of the salts contained in the bile that precipitate forming the calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The biliary lithiasis has a multifactorial genesis, with a large family component, characterized by alteration of cholesterol homeostasis and metabolism of the salts contained in the bile that precipitate forming the calculations. Cholelithiasis is often linked to hemolytic diseases that alter the solubility of bile salts, but today the form is not only increasing due to hematological diseases, but also due to the growing problem of pediatric obesity and use of particular drugs [ 6 , 7 ]. In the series, the authors took into consideration the cholecystectomies performed in patients with cholelithiasis unrelated to hemolytic diseases in order to analyze the predisposing factors and the results of the surgical treatment.…”
Section: Discussionmentioning
confidence: 99%